Clinical, Echocardiographic and Laboratory Cardiac Monitoring in Breast Cancer Patients Undergoing Chemotherapy with Anthracycline Agents: A Pilot Study on Cardioprotective Algorithms at Mohammad Hoesin General Hospital, Palembang - Indah Puspita (Majalah Kardiologi Indonesia)
Objectives We analyzed echocardiography and laboratory results of breast cancer patients undergoing chemotherapy with anthracycline agents, to find cardiotoxicity risk and prevalence among South Sumatra population.